BUILDING CHARACTER OF ALTRUISM PRAXIS IN ENGLISH CLUB AT MAN KARAWANG - Fina Aufar Laela Ibrahim (Getsempena English Education Journal, 2018)
This study aimed at investigating the altruism praxis in English club extracurricular program at Senior High School. This study employed a case study and conducted in MAN Karawang. The data in this study were the occurence of altruism aspects in one of English club annual program, which is English show-up. This study employed two instruments in collecting data, namely observation sheet and interview guide. This study revealed that two aspects of altruism, prosocial behavior and aversive-arousal reduction appeared in school English program at MAN Karawang and the most dominant is prosocial behavior. In other words, it can be concluded that MAN Karawang has contributed in that altruism praxis. The contribution is shown by adjusting students of MAN Karawang to benefit for each other, through following kind of behaviors, Student leads to write and translate the script for show-up program; Students carry the properties in and out of the stages along the show; Students set the music and scene for background of show; and Student practices each other in lack of pronunciation.